Documento di Consenso. Aggiornamenti in tema di esposizione a latice e impiego di guanti in ambito sanitario / Consensus Document. Update on latex exposure and use of gloves in Italian health care settings - Crippa, M.; Baldiani, L.; Baruffini, et al., A. (La Medicina del Lavoro, 2008)
Consensus Document. Update on latex exposure and use of gloves in Italian health care settings This consensus document was prepared by an Italian working group including occupational health professionals involved for many years in the management of glove- and latex-related problems in health care settings. The aim of this document was to address the most significant technical, epidemiological, clinical, environmental and prevention problems related to the use of gloves and latex. The group’s recommendations are based on scientific evidence and practical experience but they cannot be considered as final. These topics need to be periodically revised. The following points should be taken into account:• glove quality seems to have improved considerably but the information on glove features provided by the manufacturers is often still inaccurate or incomplete;• the regulations in force provide that the manufacturers perform tests to supply evidence for the quality of the products but they do not indicate which analytical method should be used and they do not require that the results be reported in the technical data sheets. Thus the manufacturers have only to declare that their products are “in accordance with the rules”;• therefore, purchasers should require the manufacturing companies to supply detailed information and verify their reliability. Moreover, the rules should be adapted to higher quality standards;• occupational physicians must be involved for the correct choice and purchase of protective gloves;• the use of gloves (in particular latex gloves) and latex devices in health care settings should be based on specific criteria: procedures must be available stating which kind of gloves are suitable for specific tasks.When exposure to latex cannot be avoided it is necessary to choose products that have good biocompatibility (e.g., powder free-gloves with low allergen content);• once and for all latex powdered gloves should no longer be commercially available!• labels for latex devices (including gloves) should report the extractable latex allergen content. Limit values for extractable latex allergens should be established;• the use of synthetic rubber gloves should be encouraged since some materials (e.g., neoprene and nitrile rubber) appear to have physical properties and protective efficacy similar to latex, plus good biocompatibility;• more studies should be promoted to verify the protective efficacy of new synthetic materials;• health care workers should be informed about the advisability and usefulness of using materials other than latex;• health care services should not cause additional risks but rather highlight the advantages for workers and patients if the use of latex gloves and devices is minimized.